2021
DOI: 10.2519/jospt.2021.9957
|View full text |Cite
|
Sign up to set email alerts
|

No Added Benefit of 8 Weeks of Shoulder External Rotation Strength Training for Youth Handball Players Over Usual Handball Training Alone: A Randomized Controlled Trial

Abstract: Objective To assess the effectiveness of a short (5–10 minutes) shoulder external rotation (ER) strength program, using elastic bands, in adolescent handball players. Design Randomized controlled trial. Methods The sample included 6 adolescent handball teams (3 female, 3 male) with a total of 92 players and a mean age of 16.6 years. Players were randomized within teams to an intervention group, which completed a shoulder ER strengthening program of 2 exercises performed 3 times per week after handball training… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Two interventions in handball were also studied but did not prove effective in their goal to reduce risk factors for a shoulder injury. The interventions trialed were an 8-week external rotation-focused strength training program, and the Oslo Sports Trauma Research Center shoulder injury prevention program [ 105 , 106 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Two interventions in handball were also studied but did not prove effective in their goal to reduce risk factors for a shoulder injury. The interventions trialed were an 8-week external rotation-focused strength training program, and the Oslo Sports Trauma Research Center shoulder injury prevention program [ 105 , 106 ].…”
Section: Resultsmentioning
confidence: 99%
“…Further study of training load across various sporting activities and contexts may be a promising avenue for researchers to enhance their understanding of injury risk factors and should be considered for future studies. ree studies sought to evaluate targeted shoulder injury prevention programs among youth [80,105,106]. ese were high-quality studies (RCT), where the prevention modality sought to reduce the number of injuries observed in baseball or handball.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Neuromuscular coordination has been pointed out as an important factor to consider [ 46 , 51 ]. Other variables, such as experience level and throwing automation or power have also been taken into account to explain these differences [ 52 ]. In this regard, it has been found that novice players do not reach their angular velocity peak of internal rotation until releasing the ball [ 53 ].…”
Section: Discussionmentioning
confidence: 99%